Interpersonal and institutional trust in the historical evolution of money forms - Hlushchenko, O. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2025)
Digital progress and the emergence of cryptocurrencies have led to the actualization of issues of the role of trust in the monetary system, the influence of different types of trust on the perception of different forms of money, the essence and determinants of said trust. The article presents the results of the analysis of the transformation of the role that trust plays in the formation of societal attitudes towards money in the context of the revolution of it’s form, in order to reveal the particularities of trust in cryptocurrency. The research methodology is based on the assumption that trust in different forms of money has corresponding determinants that reflect the peculiarities of these forms. The research was conducted using methods of theoretical generalization of the results of empirical research on the transformation of monetary relations and the role of trust in the adoption of digital currencies. The paper shows that each stage of change of monetary media is accompanied by a change in the dominant types of trust: from confidence in the fact that goods have inherent material value and the presence of interpersonal trust at the early stages of commodity-money relations, to institutional trust in banks, central authorities and financial institutions in modern monetary systems, and later - to trust in algorithms and protocols in decentralized networks in the era of the digital economy. Based on the analysis of the technical evolution of several blockchain generations, the characteristic features and limitations of modern cryptocurrencies are identified, in particular, high volatility, lack of institutional support, pseudo-anonymity of transactions, high dependence on user trust and significant energy and environmental costs when using a Proof-of-Work consensus algorithm. Special attention is paid to the role of interpersonal and institutional trust in shaping users’ willingness to adopt cryptocurrencies. The article summarizes the results of empirical and theoretical research, which indicate that a high level of interpersonal trust influences the adoption and implementation of cryptocurrencies, while a low level of institutional trust may stimulate the use of cryptocurrencies as an alternative means of savings and a tool for hedging economic risks.